Rudimentary Stratagems for Skilful Failures: Tactical Deployment of Humour and Play in Drawing, Sculpture, and Performance Practice - Jowitt, Joseph (Auckland University of Technology, 2026)
Through creative practice-led research, this project investigates what happens when we lean into failure, loosen the grip on optimisation, and let mischief steer the making. It explores how a playful, comedic approach might interrogate our relationship with technology, language, and materiality, and whether such strategies can offer comfort and connection in times of crisis. Can laughing in an emergency create momentary communities of understanding? Through rudimentary object-making, diagrammatic drawings, and rickety animatronics, the work riffs on familiar media meaning machines—radios, remotes, signposts—rendered as laconic stand-ins. These gestures of failure invite a seesaw of recognition and distancing, opening space for ambiguity and connective speculation. Could the rudimentary approach of a comedy ‘sketch’ develop into a productive methodology when transferred to sculptural and drawing mediums? Philosophical scaffolding in the project comes from Henri Bergson’s treatise on humour and his ideas around the tension between the mechanical and the vital. Alongside this, there is further support from Noë’s entanglement of art and life, Stiegler’s technics as prosthetic thought, and Haraway’s notion of ‘kinning’. Together, they frame humour not as embellishment but as a central disruptive, yet connective force—a way to reorganise ourselves in the ‘thick present’. The research asks: can erratum be an act of liberated resistance? Therefore, this thesis proposes play as a serious philosophical stance: a mode of thinking that scrambles habitual frameworks, embraces erratum, and proposes a speculative possibility for holding things lightly in an unstable troubled world.